A model for bridging microtubule dynamics with nuclear envelope shape evolution during closed mitosis. (November 2020) - Fang, Chao; Zheng, Fan; Yao, Jiaxing; Wei, Xi; Fu, Chuanhai; Shi, Xinghua; Lin, Yuan
Abstract: Lower eukaryotic cells such as Schizosaccharomyces pombe employ closed mitosis for their division where the nuclear envelope remains intact despite undergoing severe deformation. However, how forces generated by growing spindle microtubules overcome resistance from the deformed nuclear membrane as well as the viscous surrounding to drive the progression of closed mitosis remains unclear. In this study, by integrating microtubule dynamics with membrane elasticity and viscous cytoplasm response, we developed a mechanics model to bridge molecular activities and nuclear envelope shape evolution. It was predicted that, starting from a sphere, the nuclear envelope will undergo initial elongation, necking and final spindle poles separation to become a barbell at the end of closed mitosis, in good agreement with our experimental observations. Furthermore, these three deformation stages were found to be correlated with a gradually increased, a suddenly dropped and an almost constant poleward force generated by polymerizing microtubules. Finally, from energy analysis we showed that membrane tension plays a dominant role in resisting the deformation of the nuclear envelope while contribution from viscous dissipation is largely negligible.